2014
DOI: 10.1111/pme.12536
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Prophylactic Gabapentin and Lornoxicam in Preventing Postendodontic Pain

Abstract: Based on the obtained data, prophylactic lornoxicam controlled postendodontic treatment pain more effectively than did the placebo drugs, and gabapentin was more effective in controlling the pain than either lornoxicam or the placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Figure and Table detail the 133 trials we included in the review, with our categorisation of risks of bias in Fig. . We excluded one duplicate trial , three trials that were unavailable as full text , five trials that did not use a placebo , one trial that used combination therapy and two uncontrolled trials .…”
Section: Resultsmentioning
confidence: 99%
“…Figure and Table detail the 133 trials we included in the review, with our categorisation of risks of bias in Fig. . We excluded one duplicate trial , three trials that were unavailable as full text , five trials that did not use a placebo , one trial that used combination therapy and two uncontrolled trials .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Işik et al was not included in the present review as it was a nonoral surgery procedure, measured postendodontic pain and evaluated the efficacy of prophylactic gabapentin (600 mg) and lornoxicam (8 mg) in preventing postendodontic pain. 30 They recorded VAS scores at 4, 8, 12 and 24 hours postoperatively and reported that the pain score at 12 hours postoperatively was significantly lower in the gabapentin group than in groups receiving lornoxicam or placebo. 30 A cross-over study by Cheung et al reported greater analgesic efficacy with postoperative administration of pregabalin when compared with preoperative administration following third molar surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…30 They recorded VAS scores at 4, 8, 12 and 24 hours postoperatively and reported that the pain score at 12 hours postoperatively was significantly lower in the gabapentin group than in groups receiving lornoxicam or placebo. 30 A cross-over study by Cheung et al reported greater analgesic efficacy with postoperative administration of pregabalin when compared with preoperative administration following third molar surgeries. 25 Another study not included in this review suggested that perioperative administration of gabapentin given twice daily in patients undergoing head and neck mucosal surgery did not reduce the narcotic usage but there was a reduction in pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical model of pulpitis, administration of pregabalin reduced the medullary release of glutamate and electromyographic activity induced by the application of mustard oil to the tooth pulp [126]. In a clinical trial on patients with endodontic pain, pre-operative administration of 600 mg of gabapentin effectively reduced pain for up to 24 h after treatment [127]. It must be noted that gabapentinoids are most effective in the presence of central sensitization and that they have no anti-inflammatory effect.…”
Section: Gabapentinoidsmentioning
confidence: 99%